MEMBANGUN DESA CERDAS PEMILU UNTUK MEWUJUDKAN PEMILU TAHUN 2024 YANG IDEAL DI DESA TEBING, KECAMATAN KELAPA, KABUPATEN BANGKA BARAT: BUILDING AN ELECTION-SMART VILLAGE TO REALIZE THE IDEAL 2024 ELECTION IN TEBING VILLAGE, COCONUT SUB-DISTRICT, WEST BANGKA DISTRICT - Ardli Johan Kusuma; Anwar Ilmar; Restu Rahmawati; M Chairil Akbar Setiawan; Bahjatul Murtasidin (Jurnal Pengabdian Masyarakat Multidisiplin, 2024)
the 2024 Election. The activity was carried out in partnership with the Tebing village government, Kelapa sub-district, West Bangka Regency. This activity was carried out with the consideration that it is necessary to increase the political knowledge or insight of Tebing residents, especially in the process of elections and regional elections, so that they know and understand what elections and regional elections are. Not only that, this socialization also aims to provide Tebing residents with an understanding of how to deal with issues that have the potential to hinder the implementation of ideal elections such as black campaigns, hoax news, identity politicization and also money politics, as well as other issues. The activities carried out include conducting offline socialization about elections to Tebing Village Residents, Kelapa District, West Bangka Province with the aim that Tebing Village Residents who will later become voters can recognize elections and their objectives properly, know how to vote during elections at polling stations correctly and how to avoid fraud and hoaxes that are spread and react to them wisely so that elections run well.